2016
DOI: 10.1021/acs.inorgchem.6b01722
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nitrogen Donors in Zinc Catalysts for Lactide Ring-Opening Polymerization

Abstract: The electronic effects of nitrogen donors in zinc catalysts for ring-opening polymerization of cyclic esters were investigated. Alkyl and benzyloxy zinc complexes supported by tridentate diamino- and aminoimino phenolate ligands were synthesized, and their solid-state and solution structures characterized. The solution-state structures showed that the alkyl complexes are mononuclear, while the alkoxy complexes are dimeric with the ligands coordinated with different denticities depending on the nature of the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 108 publications
3
41
0
Order By: Relevance
“…The synergistic combination of sonocatalysis and photocatalysis, called "sonophotocatalysis"o r" photosonocatalysis" (Figure 1) depending on the focus of the author, has been reported in the literature, especially for the degradation of organic compoundsi nt he aqueous phase, [42][43][44] such as phenol and phenolic compounds, [45,46] 2-propanol, [47] naphthol blue black, [48] methylene blue, [49] reactive red 120, [50] methyl orange, [51] hydrogels, [52] textile industrial effluents, [53] pesticides from waste-water, [54] paracetamol, [55] etc.…”
Section: Sonophotocatalysis:acombination Essentially Used As An Advanmentioning
confidence: 99%
“…The synergistic combination of sonocatalysis and photocatalysis, called "sonophotocatalysis"o r" photosonocatalysis" (Figure 1) depending on the focus of the author, has been reported in the literature, especially for the degradation of organic compoundsi nt he aqueous phase, [42][43][44] such as phenol and phenolic compounds, [45,46] 2-propanol, [47] naphthol blue black, [48] methylene blue, [49] reactive red 120, [50] methyl orange, [51] hydrogels, [52] textile industrial effluents, [53] pesticides from waste-water, [54] paracetamol, [55] etc.…”
Section: Sonophotocatalysis:acombination Essentially Used As An Advanmentioning
confidence: 99%
“…developed various zinc complexes with β‐diiminates as ligand . Zinc aminophenolates from Ma et al ., Mehrkhodavandi et al ., Tolman et al . showed high activities and stereoselectivities.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Coates et al developed various zinc complexes with β-diiminates as ligand. [9] Zinc aminophenolates from Ma et al, [10] Mehrkhodavandi et al, [11] Tolman et al [12] showed high activities and stereoselectivities. Hayes and Wheaton et al developed zinc complexes bearing phosphinimines [13] and Schulz et al [14] zinc ketoiminate and βdiketiminate complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[10a] In addition to β‐diketiminate complexes, ketoiminate zinc complexes have also been explored in lactide polymerization and the influence of both steric and electronic variations of the N ‐substituents on the catalytic activity was demonstrated . Moreover, the catalytic activity of zinc complexes supported by tridentate N , N′ , O ‐chelating diamino‐ and aminoiminophenolate ligands was shown to depend on the nature of the central N‐donor function, since tertiary amines were less active compared to complexes containing a central secondary amine or imine group …”
Section: Introductionmentioning
confidence: 99%